Environmental impact of direct lithium extraction from brines - Vera, Maria Laura (2023)
Evaporitic technology for lithium mining from brines has been questioned for its intensive water use, protracted duration and exclusive application to continental brines. In this Review, we analyse the environmental impacts of evaporitic and alternative technologies, collectively known as direct lithium extraction (DLE), for lithium mining, focusing on requirements for fresh water, chemicals, energy consumption and waste generation, including spent brines. DLE technologies aim to tackle the environmental and techno?economic shortcomings of current practice by avoiding brine evaporation. A selection of DLE technologies has achieved Li+ recovery above 95%, Li+/Mg2+ separation above 100, and zero chemical approaches. Conversely, only 30% of DLE test experiments were performed on real brines, and thus the effect of multivalent ions or large Na+/Li+ concentration differences on performance indicators is often not evaluated. Some DLE technologies involve brine pH changes or brine heating up to 80 oC for improved Li+ recovery, which require energy, fresh water and chemicals that must be considered during environmental impact assessments. Future research should focus on performing tests on real brines and achieving competitiveness in several performance indicators simultaneously. The environmental impact of DLE should be assessed from brine pumping to the production of the pure solid lithium product.